2021
DOI: 10.3390/app11167643
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Static and Dynamic Compression Characteristics of Limestone Based on Its Initial Damage

Abstract: In the current work a new equation for initial damage assessment of limestone based on plane strain theory is proposed. Detailed investigations of the static and dynamic characteristics of limestone with different initial damage degree, using longitudinal wave speed, and static-dynamic compression tests are performed. This study investigated the static and dynamic characteristics of limestone with different initial damage degree, using longitudinal wave speed, and static-dynamic compression tests. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…They found that the initial damage has a significant effect on the creep behavior of rock and proposed a new nonlinear creep damage model to predict the creep behavior of sandstone under different initial damage states. Wang Yongqian et al 29 studied the static and dynamic characteristics of limestone with different initial damage degrees by using longitudinal wave velocity and static-dynamic compression test. They found that strain rate and initial damage have obvious influence on rock compression characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the initial damage has a significant effect on the creep behavior of rock and proposed a new nonlinear creep damage model to predict the creep behavior of sandstone under different initial damage states. Wang Yongqian et al 29 studied the static and dynamic characteristics of limestone with different initial damage degrees by using longitudinal wave velocity and static-dynamic compression test. They found that strain rate and initial damage have obvious influence on rock compression characteristics.…”
Section: Introductionmentioning
confidence: 99%